EFFECT OF CORPORATE SOCIAL RESPONSIBILITY (CSR), EARNING PER SHARES (EPS), AND DEBT TO EQUITY RATIO (DER) DISCLOSURE ON RETURN OF SHARES IN FINANCIAL SECTOR COMPANIES LISTED ON INDONESIA STOCK EXCHANGE: PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR), EARNING PER SHARES (EPS), DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN SAHAM PADA PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sartika Nawangsari; Adam Zakaria; Ati Sumiati (Yayasan Education and Social Center, 2021)
This study aims to determine the influence disclosure of Corporate Social Responsibility (CSR), Earning Per Shares (EPS), and Debt to Equity Ratio (DER) on stock returns in financial sector companies listed on the Indonesia Stock Exchange in 2019. The method used in this study is a documentation study method with a quantitative approach. The population of this research is 106 companies, with 62 companies used as research samples using the purposive sampling technique. To obtain research data, secondary data is used by taking annual reports and financial statements of financial sector companies listed on the Indonesia Stock Exchange in 2019. The results showed that partially the Corporate Social Responsibility (CSR) variable did not affect stock returns. The Earning Per Shares (EPS) variable also has did not affect stock returns. The variable Debt to Equity Ratio (DER) has a significant effect on stock returns. Simultaneously the variables of CSR, EPS, and DER effect on stock returns of financial sector companies. Testing the coefficient of determination is 10.3%, while other factors outside the study influence the rest. This study concludes that there is an influence between the disclosure of Corporate Social Responsibility (CSR), Earning Per Shares (EPS), and Debt to Equity Ratio (DER) on stock returns in financial sector companies listed on the Indonesia Stock Exchange in 2019